RNA silencing suppressors: how viruses fight back. (March 2008) - Shi, Yan; Gu, Mei; Fan, Zaifeng; Hong, Yiguo
RNA silencing is a collective term that refers to diverse RNA-directed processes resulting in sequence-specific degradation of target RNA and repression of gene expression, either at transcriptional or post-transcriptional levels. In animals, fungi and plants, RNA silencing represents a mechanism guided by small RNAs against virus infection. Viruses can be inducers and targets of RNA silencing, and have evolved active and passive strategies to counter the cellular antiviral mechanism. This review discusses various approaches, including protein- and RNA-mediated silencing suppression and viral escape of RNA silencing without suppression, to highlight how viruses could fight back to survive under the universal host surveillance.